STUDI EKSPERIMENTAL KUAT TEKAN CAMPURAN TANAH LATERIT DAN KAPUR (CaCO3) UNTUK LAPIS PONDASI JALAN - Irianto (Jurusan Teknik Pertambangan Program Studi S1 Teknik Pertambangan Fakultas Teknik Pertambangan dan Perminyakan Universitas Papua, 2020)
In remote areas most roads still use soil pavement which is very susceptible to weather changes, especially those using soil pavement with high plasticity or clay soil. In addition to cost issues, the difficulty of obtaining a good material source becomes another problem that results in soaring material procurement prices. Related to that matter, then conducted research that utilize local material that is limestone rock (limestone) as material of stabilization. This research is experimental by designing a mixture of lime-laterite cylinders with a diameter of 50 mm and a height of 100 mm. The number of test specimens was 144 by taking samples from two regions, namely Skyland-Jayapura and Mindiptana-Merauke and for mixtures using 5%, 10%, 15%, 20%, 30%, 40%, 60% % with lime gradation each pass 10, 40, and 200 sieves. Mixed mechanical testing was performed after the test specimen was subjected at 7 days with a compressive strength test. The results showed that the specimens for Skyland-Jayapura area with a mixture of laterite soil + lime pass filter 200 were in lime variations of 5% valued at 0.46 MPa, while laterite + lime clearance 40 was in lime variation of 5% 0 , 64 MPa.